Nanocrystalline TiO2 Films: Synthesis and Low-Temperature Luminescent and Photovoltaic Properties - Serikov, T.M.; Ibrayev, N.Kh.; Isaikina, O.Ya.; Savilov, S.V. (Russian Journal of Inorganic Chemistry, 2021)
Nanocrystalline TiO2 films of different morphology have been fabricated using various experimental approaches. Photoluminescent properties of films at 90 K have been studied. The effect of heat treatment on low-temperature properties caused by the anatase–rutile phase transition has been demonstrated. It has been shown that the luminescence of rutile films is longer, for both TiO2 nanoparticles and nanotubes. Photovoltaic cells of the DSSC type have been assembled on the basis of the obtained nanostructures. Impedance spectroscopy has demonstrated that the resistance to electron transport in films of TiO2 nanotubes is higher and the recombination rate is lower than in films of nanoparticles.
Keywords: nanoparticle; nanotube; titanium dioxide; uminescence; dye-sensitized solar cell; photovoltaics; luminescence spectroscopy